Un ensemble funéraire de l’Antiquité tardive à dépôt atypique d’âne à Woippy (Moselle) - Gaël Brkojewitsch; Olivier Putelat (Gallia, 2022)
During the Roman period, the Woippy area was linked to the city capital Metz/Divodurum. This area, traversed by the main road Lyon/Lugdunum-Trier/Augusta Treverorum, was occupied by Roman settlements, including a large villa, near which a burial complex, located along the edge of the road and consisting of eight graves, was established during Late Antiquity. The graves were likely laid out over one or two generations between the years 360 and 440. The young adults and adults buried therein, were, in some cases, deposited in assembled wooden chests within large rectangular pits, resulting in the decomposition of soft-tissue in an empty space. The primary nature of the deposits is attested to; the subjects are laid on their backs, with their arms and legs outstretched, the forearms extended alongside the body or drawn over the pelvis, within a container large enough to also place material culture. The burials are neatly organised in rows and follow a rather strict north-south orientation. The rows run parallel to the Roman roadway, which suggests a general management of the area. Additionally, the absence of overlapping burial implantation is an indication of the existence of topographical markings made of organic material. The material culture is not abundant and, on average, the graves contain 3.5 objects. The deposits consist mainly of glassware and, to a lesser extent, ceramic vessels as well as, in two cases, belt parts placed beside the body. The vessels are related to food consumption (bowls, pots, terrines) and liquids (jugs, beakers, bottles). In four burials, food remains were identified, which indicate the presence of bread, cakes or cereal-based porridge. It also appears that the burial area developed around a hierarchically elevated grave containing the burial (no 1) of a probable young adult male. The remains were accompanied by five objects that rank this grave above average for the group in terms of burial wealth, without outperforming the whole. The donkey deposit within the burial complex is the most atypical element. An archaeozoological study and a palaeogenetic analysis made it possible to identify the equine remains as belonging to an adult male donkey, between 5 and 6 years of age at the time of death and of fairly good stature (1.45 m on average). Perhaps slaughtered during a prior ceremony, this animal was also accompanied by material goods and was perfectly integrated into the row organisation of the burial space. The animal was in its prime, and thus represents a significant contribution dedicated to this person who clearly possessed a particular status within the group. Several clues allow us to relate the two deposits, notably their perfect symmetry, as well as the batches of rough ceramics from Speicher, present in both, and absent from the other tombs. Insofar as the human burial can be chronologically anchored to the earliest occupation phase of the funerary complex (between 360 and 410), the preferred hypothesis is that of a founding burial, accompanied by the donkey burial, around which the other burials were clustered. The Woippy site is therefore an example of a small-scale rural burial site from Late Antiquity. In terms of the chronological attribution and duration of its occupation, this ensemble is very similar to the regional site of Uckange. Despite the homogeneity of material on a regional scale, the convergences between the ensembles of La Hache in Cutry and Fontoy are also noteworthy. The intentional donkey deposit, spectacularly installed in perfect alignment with the deceased human, as well as the integration of the whole within the very heart of this funerary ensemble clearly points to the funerary, sacrificial or symbolic sphere and render this context a unicum on the scale Gaul during Late Antiquity.